Lower limb immobilization device induced small setup errors in the radiotherapy. Issue 15 (April 2018) - Lu, Yuting; Ni, Xinye; Yu, Jingping; Ni, Xinchu; Sun, Zhiqiang; Wang, Jianlin; Sun, Suping; Wang, Jian
Abstract : Abstract: The aim of this study was to design a lower limb immobilization device and investigate its clinical application in the radiotherapy of the lower limbs. Around 38 patients who underwent lower limb radiotherapy using the designed immobilization device were included in this study. The setup errors were calculated by comparison of the portal images and the simulator films or digital reconstructed radiographs (DRRs). From all 38 patients accomplished the radiotherapy using this device, 178 anteroposterior portal images and 178 lateral portal images were used for the analysis of the positional accuracy. Significant differences were observed in the setup error of the head–foot direction compared with the left–right direction ( t  = 3.404, P =  .002) and the anterior–posterior directions ( t  = 3.188, P =  .003). No statistical differences were identified in the setup error in the left–right direction and anterior–posterior direction ( t  = 0.497, P =  .622). The use of the in-house designed lower limb immobilization device allowed for relatively small setup errors. Furthermore, it showed satisfactory accuracy and repeatability.